Manajemen Projek Teknologi Informasi Pengembangan Website UMKM PMAM Bali - I Gede Juliana Eka Putra; I Kadek Setiawan; I Wayan Angga Surya Lodinata (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2021)
Website based online store is one of the Information Technology which is a business strategy platform for selecting and maintaining customers, can optimize long-term value, can store customer philosophy and culture to support the effectiveness of marketing, sales and service processes. Building a good online store must follow the correct project procedure, which is preceded by making a proposal to outline all the requirements that will be implemented in making the intended application. At this writing, the author prepared a website-based online shop proposal for Umkm PMAM Bali which described in detail the scope of the platform to be built (Scope), the functions to be made which are described by the Work Breakdown Structure (WBS), the implementation schedule (Schedule). Resources (Resources), cost plans (Cost), risk analysis (Risk Analysis) and forms of change management (Change Management) when the application is ready to operate. This proposal is expected to be able to provide input for building the website platform and will be proposed to Umkm PMAM Bali to be used and implemented.